Exploring Religiosity as Mediator of The Association Between Democratic Parenting, Peer Support, and Self-Concept Among Adolescent Moral Literacy - Masitah, Widya; Alsa, Asmadi; Partino, Partino; Madjid, Abd. (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study aims to examine the influence of democratic parenting, peer support, and self-concept on moral literacy through the mediator of religiosity in adolescents. By using a quantitative approach, data collection methods through scale techniques, namely: moral literacy scale, religiosity scale, democratic parenting scale, peer support scale, and self-concept scale. The sampling technique was based on purposive sampling, the research respondents totaled 688. Data analysis using Structural Equation Modeling (SEM) with the help of the AMOS software computer program. The results showed: that (1) Democratic parenting, peer support, and self-concept have a positive and significant effect on religiosity. (2) Democratic Parenting, Peer Support, and Self-Concept have a positive and significant effect on Moral Literacy. Likewise, Religiosity has a positive and significant effect on Moral Literacy. Thus the researcher's hypothesis is accepted that religiosity is the right mediator to be able to improve adolescent moral literacy which is influenced by the 3 variables tested. This study recommends parents' attention to increasing adolescent religiosity in addition to choosing to use democratic parenting for adolescents to develop adolescent moral literacy.